2020
DOI: 10.3390/polym12040783
|View full text |Cite
|
Sign up to set email alerts
|

Ag NPs-Assisted Synthesis of Stable Cu NPs on PET Fabrics for Antibacterial and Electromagnetic Shielding Performance

Abstract: In this study, Cu/Ag/polydopamine (PDA)/polyester (PET) fabrics were fabricated for multi-functional textiles. The PET fabrics were firstly modified by dopamine to form a polydopamine (PDA) layer on the fiber surface, then Ag nanoparticles (Ag NPs) were anchored on fiber surface through chelation between PDA and Ag+ ions, and the Ag NPs were further used as catalytic seeds for in situ reduction of Cu nanoparticles (Cu NPs). The surface morphology, chemistry, and crystalline structure of the prepared PET fabric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 36 publications
1
12
0
Order By: Relevance
“…The results are shown in Figure 8B. As shown in the figure, AgNO 3 -soaked PET, PET@PDA@Ag, and PET@PDA@nHA&Ag artificial ligaments had a certain antibacterial effect after reacting with the AgNO 3 solution of a certain concentration, which was similar to previous literature reports (Wang K. et al, 2020), and the antibacterial ability increased with the increase of AgNO 3 reaction concentration, which indicated that the increase of silver ion concentration in the reaction solution had an obvious promoting effect on the antibacterial effect of the artificial ligament. On the other hand, it can also be observed that before the interaction with silver ions, the antibacterial ability of three kinds of ligaments also has an obvious difference.…”
Section: Release Of Silver Ion and Antibacterial Propertiessupporting
confidence: 88%
See 1 more Smart Citation
“…The results are shown in Figure 8B. As shown in the figure, AgNO 3 -soaked PET, PET@PDA@Ag, and PET@PDA@nHA&Ag artificial ligaments had a certain antibacterial effect after reacting with the AgNO 3 solution of a certain concentration, which was similar to previous literature reports (Wang K. et al, 2020), and the antibacterial ability increased with the increase of AgNO 3 reaction concentration, which indicated that the increase of silver ion concentration in the reaction solution had an obvious promoting effect on the antibacterial effect of the artificial ligament. On the other hand, it can also be observed that before the interaction with silver ions, the antibacterial ability of three kinds of ligaments also has an obvious difference.…”
Section: Release Of Silver Ion and Antibacterial Propertiessupporting
confidence: 88%
“…Silver ions could bond with protein through the sulfur/nitrogen/oxygen atom on the amino acid side chain, which causes the destruction of cell membrane function and leads to the inhibition of bacterial growth ( Lemire et al, 2013 ). In recent years, the silver antibacterial medical products, such as silver ion dressing, have been certified by FDA and used in surgery ( Chernousova and Epple, 2013 ), and silver nano-particles were used in antibacterial modification of PET artificial ligament ( Wang K. et al, 2020 ). Antibacterial ability of silver has following characteristics, such as broad-spectrum and sustained release, which make silver good candidate for antibacterial materials of artificial ligament.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to viruses, textiles are common substrates for bacterial growth, under proper temperature and humidity condition [ 186 ]. Those impregnated with Ag and Cu NPs had dramatically enhanced antibacterial properties when compared to unimpregnated PET textile [ 187 ]. Similarly, studies on cotton textiles impregnated with Ag NPs, and those impregnated with a mixture of Ag and Cu NPs, both exhibited excellent antibacterial and antifungal properties [ 188 ].…”
Section: Coatings On Substratesmentioning
confidence: 99%
“…For instance, NP dispersions can be coated onto cotton fibers by means of pad dyeing [ 132 ], immersing [ 191 ], or ironing [ 190 ], all of which are traditional coating methods in the textile industry. Chemical reduction [ 192 ] is another commonly used treatment method: Ag and Cu NPs can be deposited onto PDA/PET fabrics by the chemical reduction of aqueous Ag and Cu salt solutions [ 187 ]. However, the problem for NPs loaded onto textiles is that they are poorly bonded, and tend to fall off during washing, leading to the loss of antimicrobial properties.…”
Section: Coatings On Substratesmentioning
confidence: 99%
“…These Ag NPs, as catalytic seeds, facilitated deposition of Cu NPs on the surface of fabrics through chemical copper plating. Thus, PDA, functioning as template, expedited Cu NPs deposition onto the surface of fabric that displayed killing of most of the adhered bacteria ( Wang K. et al, 2020 ).…”
Section: Cationic Charge Enriched Pda-fabricated Surfaces: Effect Onmentioning
confidence: 99%